Polycomb group (PcG) proteins prevent the assembly of abnormal synaptonemal complex structures during meiosis - Feijão, Tália (2022)
Copyright © 2022 the Author(s). Published by PNAS. This article is distributed under Creative Commons Attribution-NonCommercial-NoDerivatives License 4.0 (CC BY-NC-ND).